Chemical state analysis using Auger parameters for XPS spectrum curve fitted with standard Auger spectra. (2nd March 2018) - Shima, Masahide; Tsutsumi, Kenichi; Tanaka, Akihiro; Onodera, Hiroshi; Tanemura, Masaki
Abstract : Chemical state analysis is quite important in X‐ray photoelectron spectroscopy. Auger parameter analysis is one of the useful methods to analyze the chemical state in X‐ray photoelectron spectroscopy, because it is not necessary to take the charging effect into account for the analysis of nonconductive materials, especially for the simple material systems of a single chemical state. For the analysis of complicated complex systems, here, we developed the Auger parameter analysis combined with the curve fitting calculation using standard Auger spectra. Copper oxide complexes consisting of a mixture of CuO and Cu2 O oxide states were formed on copper platelets by annealing in atmospheric ambient. For those samples, by combining the curve fitting using standard Cu, CuO, and Cu2 O Auger spectra, two oxide states were clearly distinguished in the Auger parameter analysis. Thus, this advanced Auger parameter analysis is believed to be promising for the chemical state analysis of complicated complex systems.